Descriptive Drinking Norms and Alcohol-Related Negative Consequences: A Moderated Mediation Model Involving Drinking Quantity and Protective Behavioral Strategies - Vera, Belén del Valle (Journal of drug issues, 2025)
We examined whether drinking quantity mediated the relationship between descriptive drinking norms and alcohol-related negative consequences, and if this was moderated by protective behavioral strategies (PBS) use. Undergraduate students (n = 538, 78.0% female, mean age = 21.21 [SD = 3.62]) from three Spanish universities completed a questionnaire. Simple and moderated mediation analyses were conducted. Drinking quantity fully mediated the relationship between descriptive drinking norms and alcohol consequences, and PBS moderated this relationship. Among participants with high PBS use, the impact of descriptive drinking norms on drinking quantity disappeared. The indirect effect of descriptive drinking norms on alcohol consequences through drinking quantity was significant for individuals with low/moderate PBS use levels, but not for those with high PBS use. Our findings shed light on how descriptive drinking norms influence alcohol-related negative consequences, and suggest that promoting the utilization of PBS could be an effective approach to ameliorate the impact of peer influences on drinking behavior.